2022
DOI: 10.1371/journal.pcbi.1010516
|View full text |Cite
|
Sign up to set email alerts
|

Ten simple rules for creating and sustaining antiracist graduate programs

Abstract: In 2020, the combination of police killings of unarmed Black people, including George Floyd, Breonna Taylor, and Ahmaud Arbery, and the Coronavirus Disease 2019 (COVID-19) pandemic brought about public outrage over long-standing inequalities in society. The events of 2020 ignited global attention to systemic racism and racial inequalities, including the lack of diversity, equity, and inclusion in the academy and especially in science, technology, engineering, mathematics, and medicine (STEMM) fields. Racial an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Research plays a critical role in advancing DEI in higher education. It provides an evidence-based foundation for understanding the challenges and opportunities associated with promoting DEI and for identifying effective strategies to address them (Perez-Lopez, et al, 2022). For instance, a study conducted by Chang et al (2014) found that student interaction with diverse peers was positively associated with gains in critical thinking, problemsolving, and leadership skills.…”
Section: The Role Of Research In Advancing Diversity Equity and Inclu...mentioning
confidence: 99%
“…Research plays a critical role in advancing DEI in higher education. It provides an evidence-based foundation for understanding the challenges and opportunities associated with promoting DEI and for identifying effective strategies to address them (Perez-Lopez, et al, 2022). For instance, a study conducted by Chang et al (2014) found that student interaction with diverse peers was positively associated with gains in critical thinking, problemsolving, and leadership skills.…”
Section: The Role Of Research In Advancing Diversity Equity and Inclu...mentioning
confidence: 99%
“…Ten Simple Rules are more to develop soft skills, career promotion/advancement (how to organize a scientific conference [ 9 ], write your cover letter [ 10 ], write a literature review [ 11 ], etc. ), or other broad issues in scientific practice (e.g., models for successful collaboration [ 12 , 13 ], developing scientific communities [ 14 ], or practicing inclusive science [ 15 , 16 ]).…”
Section: Introductionmentioning
confidence: 99%